Vulnerability Of Interlanguage System: A Case Study Of Students Learning English As A Foreign Language InSMP Muhammadiyah 1 Surakarta - Wijayanti, Shelfi Apri; , Prof. Dr. Endang Fauziati, M. Hum.; , Dra. Dwi Haryanti, M. Hum (2013)
The current research deals with the vulnerability of inter language (IL) system of SMP Muhammadiyah 1 Surakarta students towards the influences of native language/L1 (Indonesian) system and target language/L2 (English) system. The objectives of the research are to identify: 1) how the influence of native language (Indonesian) linguistic system to the students' inter language system is, 2) how the influence of target language (English) linguistic system to the students' interlanguage system is, 3) to what extend the students' native language (Indonesian) system influence their interlanguage system, 4) to what extend the target language (English) system influence the students' interlanguage system and 5) the ratio of L1 (Indonesian) influence to L2 (English) influence on the students' interlanguage system. The research is a descriptive qualitative research. The data and data source of the research is the erroneous sentences found in English compositions written by two classes of grade VIII students in 2012/2013 academic year in SMP Muhammadiyah 1 Surakarta. The data collection techniques are elicitation and documentation. The data analysis techniques are collecting data, identification and list of error, classification into error types, analysis of the source of error, description of the influence degree and drawing conclusion. The writer utilizes the interlanguage (IL) theories by Selinker, Rutherford, Adjémian, Ellis and Corder as well as the error analysis (EA) framework by Shridar, James, and Corder. The study reveals that the students' IL systems are vulnerable to the L1 and L2 influences. The L2 influence is having much higher percentage than the L1's which implies that the students are in the right track within their IL developing stages towards L2 system. The results of the study show that (1) the influence of native language/L1 (Indonesian) linguistic system to the students' IL system are involving morphological influence and syntactic influence, (2) the influence of target language/L2 (English) linguistic system to the students' IL system are involving morphological influence and syntactic influence, (3) the total number of L1 (Indonesian) influence percentage is 32.5% consisting of morphological influence (20.37%) and syntactic influence (12.4%), (4) the total number of L2 (English) influence percentage is 67.47% consisting of morphological influence (55.32%) and syntactic influence (12.4%) and (5) the ratio of L1 (Indonesian) influence to L2 (English) influence is 1:2.07